Instanteneous Multi-Baseline Ambiguity Resolution with Constraints - Buist, P.; Teunissen, Peter; Giorgi, G.; Verhagen, S. (Curran Associates, 2008)
Traditionally the relative positioning and attitude determination problem are treated as independent. In this contribution we will investigate the possibilities to use multiantenna data, not only for attitude determination, but also for the relative positioning. The developed methods are rigorous and have an additional advantage that they improve the ambiguity resolution on the unconstrained baseline and the overall success rate of ambiguity resolution between a number of antennas